2018
DOI: 10.1589/jpts.30.361
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracorporeal shock wave therapy on upper extremity muscle tone in chronic stroke patients

Abstract: [Purpose] The purpose of this study was to examine the effects of extracorporeal shock wave therapy (ESWT) on upper extremity muscle tone in chronic stroke patients. [Subjects and Methods] For this study, 30 stroke patients participated in this study and they were divided into ESWT group and sham-ESWT group, each group consisted of 15 patients. ESWT and sham-ESWT was performed by the patients for two times a week, for eight weeks. MyotonPRO was used to measure muscle tone. [Results] According to the results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…As supported by radiological [ 33 ] and histological [ 34 ] approaches, the structural changes in paraspinal muscles are in the foreground [ 7 ]. Furthermore, Park et al [ 35 ] found differences in cervical muscle frequency and stiffness between patients with cervicogenic headache and healthy individuals, but not in decrement as observed in our patients, which could mean that elasticity does fit the same behavior pattern as other mechanical properties when spinal muscles are assessed. This author also reported a case study [ 36 ] of an axSpA patient, analyzing cervical muscles pre- and post-treatment for central and unilateral posteroanterior mobilization.…”
Section: Discussionsupporting
confidence: 62%
“…As supported by radiological [ 33 ] and histological [ 34 ] approaches, the structural changes in paraspinal muscles are in the foreground [ 7 ]. Furthermore, Park et al [ 35 ] found differences in cervical muscle frequency and stiffness between patients with cervicogenic headache and healthy individuals, but not in decrement as observed in our patients, which could mean that elasticity does fit the same behavior pattern as other mechanical properties when spinal muscles are assessed. This author also reported a case study [ 36 ] of an axSpA patient, analyzing cervical muscles pre- and post-treatment for central and unilateral posteroanterior mobilization.…”
Section: Discussionsupporting
confidence: 62%
“…The enrolled studies were subdivided in terms of the localization of the spasticity into upper or lower limb. A total of 22 studies including 468 post-stroke adults—11 reports with the upper limb (267 patients) [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] and 10 reports within the lower limb (201 patients) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ], as well as one report including both upper and lower limbs [ 56 ]. Figure 1 presents low diagram for selection process and identification of studies for inclusion in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al (2018) [ 43 ] in their randomized study enrolled a group of 30 patients after stroke which was divided into ESWT group ( n = 15) and placebo-ESWT group ( n = 15). Both ESWT (wrist flexors = 1500 pulses, and plantar interosseous = 3200 pulses, 800 per each muscle; 1.5 bars and 0.03 mJ/mm 2 ) and sham-ESWT (only a sound of shocks) interventions were performed (eight sessions, two times per week).…”
Section: Resultsmentioning
confidence: 99%
“…The PRISMA diagram (see Figure 1) summarizes the results of the scientific literature search. Sixteen randomized controlled trials were included: these were by Bae et al, 15 Santamato et al, 16 Fouda et al, 17 Dymarek et al, 18 Kim et al, 19 Li et al, 20 Yoon et al, 21 Duan et al, 22 Guoxing et al, 23 Guo et al, 24 Fouda et al, 25 Kamaluddin et al, 26 Park et al, 27 Wu et al, 28 Ahmed et al, 29 and Li et al 30 Studied identified but not included are shown in Appendix 2. No author responded when contacted for additional information.…”
Section: Resultsmentioning
confidence: 99%